Curriculum innovation at SMKN 3 Bandung: Bridging education and industry - Syifa Nur Azizah Suhud (Himpunan Pengembang Kurikulum Indonesia, 2025)
A well-structured vocational curriculum should prepare students not only with academic knowledge but also with practical skills and competencies that align with industry standards. This study focuses on analyzing curriculum innovation at SMKN 3 Bandung, with an emphasis on the integration of the Teaching Factory (TeFa) program, which bridges the gap between education and real-world industry practices. Tefa involves collaboration with industry partners to create a simulated industrial environment, where students gain hands-on experience while still in school. Through qualitative research methods, including interviews and observations with the school’s curriculum staff, this study reveals how SMKN 3 Bandung applies the Merdeka Curriculum in line with industry needs. The curriculum structure incorporates a combination of technical skills and soft skills development, ensuring students are well-prepared for future employment. Industry partners play a crucial role in shaping the curriculum and offering students opportunities to obtain industry certifications. Despite challenges such as adapting to rapidly changing industry demands, SMKN 3 Bandung has successfully integrated practical learning experiences that enhance students’ employability and equip them better to succeed in the workforce. Abstrak Kurikulum vokasi yang baik tidak hanya membekali peserta didik dengan pengetahuan akademik, tetapi juga keterampilan dan kompetensi praktis yang sesuai dengan standar industri. Penelitian ini berfokus pada analisis inovasi kurikulum di SMKN 3 Bandung, dengan menekankan integrasi program Teaching Factory (TeFa) yang menghubungkan dunia pendidikan dengan praktik industri nyata. Tefa melibatkan kolaborasi dengan mitra industri untuk menciptakan lingkungan industri simulasi, di mana peserta didik mendapatkan pengalaman langsung saat masih di sekolah. Melalui metode penelitian kualitatif, termasuk wawancara dan observasi dengan staf kurikulum sekolah, penelitian ini mengungkapkan bagaimana SMKN 3 Bandung menerapkan Kurikulum Merdeka yang disesuaikan dengan kebutuhan industri. Struktur kurikulum menggabungkan pengembangan keterampilan teknis dan soft skills, memastikan peserta didik siap menghadapi dunia kerja. Mitra industri memiliki peran penting dalam membentuk kurikulum dan memberikan kesempatan bagi peserta didik untuk memperoleh sertifikasi industri. Meskipun ada tantangan seperti menyesuaikan dengan tuntutan industri yang berkembang pesat, SMKN 3 Bandung berhasil mengintegrasikan pengalaman belajar praktis yang meningkatkan daya saing peserta didik di dunia kerja. Kata Kunci: inovasi kurikulum; kolaborasi industri; Kurikulum Merdeka; teaching factory